Total talar prosthesis with and without ankle ligament reconstruction using the three-dimensional computer-aided design and computer numerical control manufacturing techniques - Chayanin Angthong; Prasit Rajbhandari (My University, 2020)
Severe damage and bone loss of the talus are problematic issues because of its unique shape, function, and characteristics. This present study’s objective is to propose the process of customized total talar prosthesis manufacturing, using three-dimensional (3D) Computer-Aided Design (CAD) with Computer Numerical Control (CNC) production along with evaluation of the results of total talar prosthesis replacement with or without ankle ligament reconstruction in patients with severe conditions of talus. The case series included five patients (mean age: 27.6 years) with severe talar loss or damage. The mean follow-up time was 17.8±8.4 months. Related complications were: i) mild subsidence in 1 patient (20%) and ii) periprosthetic fracture in another patient (20%). The mean clinical scores including VAS-FA and SF-36 were improved following surgeries. Customized total talar prosthesis appears to provide satisfactory outcomes for the treatment of severe talar loss or damage at a short-term follow-up.
Keywords: Ankle replacement; Foot and Ankle Surgery